Predictors for conversion in Laparoscopic Nephrectomy - Koju, Rajan; Sharma, Vijay; Shah, Arun (Nepalese Journal of Cancer, 2025)
Objective: Laparoscopic nephrectomy is preferred surgery to treat patient with renal mass and Nonfunctioning kidney (NFK) secondary to urolithiasis/ PUJO/ureteric stricture. Main objective of this study was to assess risk associated with conversion of laparoscopic nephrectomy in patient undergoing laparoscopic nephrectomy in our university hospital. Material and Methods: This was retrospective descriptive observational study which included 78 patients diagnosed with NFK by CT IVU and diuretic DTPA renogram, renal mass by CT IVU presented to Dhulikhel hospital from 1st January 2023 to 15th May 2025. Patients were reviewed in terms of demographic characteristics and clinical presentation. Statistically correlated with conversion and laparoscopic group which was analyzed by using student’s t-test and fischer exact test. Results: Mean age was 48.69 ± 14.18 years, 42 female (53.85%) and 36(46.15%) male patients. Mean operative duration was 238.5±68.68 minutes in conversion whereas in laparoscopic group was 177.06±43.99 minutes, p<0.05. Mean hospital stay was 6.5±0.53 vs 3 days in conversion vs laparoscopic group, p<0.05. Statistically significant correlation noted between conversion and laparoscopic group in terms of BMI, PCN, SSI with p<0.05. Recurrent UTI and visceral injury were not associated with conversion, p>0.05. Conclusion: Recurrent UTI, intra-operative visceral injury was not associated with conversion. BMI, PCN, Blood transfusion and SSI was significantly high in conversion group.